Voluntary Disclosure Program (PPS) Reviewed from the Perspective of State Administration Law and Its Effectiveness in Encouraging National Economic Improvement - Elyani; Khairun Na’im; Uswatun Hasanah; Andi Nova Bukit; Waruwu, Khamo (Arkus, 2023)
The voluntary disclosure program (PPS) was created to increase taxpayer compliance and the need for large funds to overcome financial deficits due to the pandemic and post-Covid economic recovery. The purpose of this research is to discuss how the legal perspective of state administration views the voluntary disclosure program (PPS). In addition, it also examines how the effectiveness of voluntary disclosure programs (PPS) in encouraging National economic improvement. The results obtained from this research are that in terms of procedures and principles, the voluntary disclosure program already represents the implementation of tax law which is part of state administrative law. Furthermore, the effectiveness of the implementation of the voluntary disclosure program (PPS) is considered ineffective. This is due to several obstacles, both in terms of the variables supporting its successful tax amnesty, which have not been implemented optimally, and the conditions of business actors who experience several obstacles, including high tariffs, limited investment instruments, many tax assets that are not liquid, and economic recovery that has not been maximized.